Spinal Extradural Arachnoid Cyst: A Case Report - Koirala, Puspa Raj; Rajbhandari, Binod; Sedain, Gopal; Shilpakar, Sushil Krishna (Nepal Journal of Neuroscience, 2018)
Spinal extradural arachnoid cyst is a rare cause of spinal cord compression resulting in spinal myelopathy. We report a case of 12-year-old boy diagnosed with extradural thoracolumbar spinal arachnoid cyst presenting with back and leg pain, progressive left leg weakness, mild muscular atrophy and difficulty in walking. The boy presented with progressive weakness of distal left lower limb and intermittent claudication. MRI-scan revealed an extramedullary non-enhancing fluid signal intensity lesion with cord compression. The patient underwent zip laminectomy from T9 - L2 level using electric drill and total excision of the extradural cyst, microsurgical repair of the dural defect, followed by laminoplasty, using ethibond sutures was done. Intraoperative finding revealed an elongated 10 cm long cystic lesion with finger-like projections extending in the extradural space from T9 - L2 level, causing significant compression and displacement of the cord. The cyst was in communication with intradural subarachnoid space with a small ovoid-shaped arachnoid opening at T12 level on the left side adjacent to T11 nerve root. The postoperative course was uneventful and patient was discharged on postoperative day seven. Neurologically, the patient showed some improvement. On one-month follow-up, there was remarkable improvement in movement of the lower limbs. He was able to walk independently without limping gait; however, he still had mild weakness in his left leg (4+/5). Nepal Journal of Neuroscience, Volume 15, Number 2, 2018, Page: 49-54